الاقتصاد الإسلامي: حفرية مصطلح - عبد الرزاق بلعباس (International Institute of Islamic Thought, 2014)
يهدف البحث إلى استكشاف الحيثيات التي صاحبت استخدام مصطلح "الاقتصاد" وانتشاره في الأدبيات العربية والإسلامية، وإلحاق صفة "الإسلامي" به؛ ما أفرز مصطلح "الاقتصاد الإسلامي". خلص البحث إلى أنّ استخدام مصطلح "الاقتصاد" لم ينبع من رحم الحضارة العربية والإسلامية، إنّما بسبب تعريب المصطلح الفرنسي (économie politique) (الاقتصاد السياسي)، فنجم عن ذلك قطيعة معرفية تجلّت -بصورة خاصة- في الإعراض عن مصطلح "المعاش"، الذي كان متداولاً في كتابات التراث العربي الإسلامي؛ ونجم كذلك تضمينٌ إدراكيٌّ حصر البحث العلمي في الاقتصاد الإسلامي، وتطبيقاته المعاصرة في فضاء النظرية الاقتصادية السائدة وفروضها الأساسية؛ ممّا حدّ من عطائه، وأعاق بلورة نظرته المقاصدية التي تتجلّى في أداء حقوق الله وحقوق العباد. The purpose of this study is to explore the conditions that accompanied the use and dissemination of the concept of economics in Arabic and Islamic literature and its junction with the adjective «Islamic», which has led to the concept of «Islamic economics». The study concludes that the adoption of the concept of economics has not been generated by Arabic and Islamic civilizational matrix, but rather the translation of the French concept of «économie politique». This led, on the one hand, to an epistemological break that gradually substituted the concept of economics to «ma'ach» adopted by the Arabic and Islamic heritage, and, on the other hand, to embed the Islamic economic research and its contemporary applications in the mainstream economic thinking and its hypotheses; which has limited its perspective and constrained its teleological vision characterized by the fulfillment of the rights of God and those of the humans.